Design and development of a novel triphibian quadcopter - Prajwal Shenoy, T; Praveen Shenoy, K; Khan, Lukhman; Aziz, Sabdar; Afran, Sayed; Kumar, Kamlesh (International Journal of Engineering and Technology, 2018)
Multimodal Vehicles can travel in at least two distinctive modes of transportation, be it air and water, land and water or air and land. In this paper, design and development of a novel unmanned multimodal vehicle is presented that can travel in air, land and water, also called a as a triphibian quadcopter which would prove beneficial in rescue operations and operations involving hazardous environments. The vehicle is essentially a mix of unmanned aerial vehicle, unmanned ground vehicle and unmanned surface vehicle and is equipped with mechanisms to travel in land, air and water at the will of the operator. The entire framework of the vehicle is built on the multi rotor configuration. Flight tests were conducted to validate the design.Â Â